Analyzing Students’ Reading Needs through Dayak Cultural Content in East Kalimantan - Royanti; Yustina Fitriani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2025)
The integration of local culture into English reading instruction is important for enhancing student engagement, reading comprehension, and cultural awareness. In Indonesia, English reading materials are predominantly influenced by foreign cultures, while locally relevant resources remain scarce. This study aims to analyze students’ reading needs to improve comprehension and strengthen cultural identity through the development of reading materials based on Dayak culture, an indigenous ethnic group from East Kalimantan. Using a mixed-methods design, data were collected from 348 students and 36 lecturers across higher education institutions in East Kalimantan through questionnaires and in-depth interviews with 10 students and 5 lecturers. The research instruments were developed based on Hutchinson and Waters’ Needs Analysis framework, addressing necessities, lacks, and wants. The findings reveal strong support for integrating local cultural texts, especially folktales and descriptive passages, to increase motivation and improve reading comprehension. Students reported difficulties with text complexity, while lecturers faced limited access to contextualized materials and low student interest in reading. Both students and lecturers preferred culturally relevant and visually engaging materials. There was a strong preference for the use of structured reading strategies such as SQ3R. These results can inform the development of culturally responsive reading materials and have implications for curriculum development, instructional design, and future research in English as a Foreign Language (EFL) context.